PROPOSAL FOR A DIRECTIVE OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL OF 5 FEBRUARY 2013 ON THE PREVENTION OF THE USE OF THE FINANCIAL SYSTEM FOR THE PURPOSE OF MONEY LAUNDERING AND FINANCING TERRORIST ACTIVITY - Marek Zieliński (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
The problem of combating money laundering was early recognized by the European Union. In 1991 the EU 1st Money Laundering Directive was published. Next, in 2001 and 2005 it was necessary to regulate this problem in details. The central goal of this paper is to analyse the EU 4th Money Laundering Directive connected to combating of money laundering and terrorist financing from different points of view. It is important that this directive is based on the 40 FATF Recommendations of 16 February 2012.